1990
DOI: 10.1101/gad.4.10.1650
|View full text |Cite
|
Sign up to set email alerts
|

Activity and tissue-specific expression of the transcription factor NF-E1 multigene family.

Abstract: NF-E1, a DNA-binding protein that recognizes the general consensus motif WGATAR, is the first tissue-specific factor to be identified in erythroid cells. Using a probe from the murine GF-1 (NF-E1) cDNA clone, we isolated three homologous chicken cDNAs: One of these corresponds to an mRNA (NF-Ela) that is abundantly and exclusively expressed in erythroid cells; a second mRNA (NF-Elb) is also expressed in all developmental stages of erythroid cells but is additionally found in a limited subset of other chicken t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
508
0
3

Year Published

1994
1994
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 602 publications
(519 citation statements)
references
References 72 publications
8
508
0
3
Order By: Relevance
“…GATA-2 mRNA was also found in cells differentiating along the erythroid, megakaryocytic and mast cell lineage pathways (Yamamoto et al 1990;Zon et al 1991;Dorfman et al 1992). The unique and indispensable contribution of GATA-2 to these lineages was confirmed by targeted disruption of the mouse GATA-2 gene, wherein it was shown that the GATA-2-null mouse did not develop haematopoietic cells (Tsai et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…GATA-2 mRNA was also found in cells differentiating along the erythroid, megakaryocytic and mast cell lineage pathways (Yamamoto et al 1990;Zon et al 1991;Dorfman et al 1992). The unique and indispensable contribution of GATA-2 to these lineages was confirmed by targeted disruption of the mouse GATA-2 gene, wherein it was shown that the GATA-2-null mouse did not develop haematopoietic cells (Tsai et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The conditions for binding and electrophoresis were as described previously (Yamamoto et al 1990). Anti-MafK antibody (Igarashi et al 1995b) and anti-p45 antibody (Igarashi et al 1995a) were incubated with nuclear extracts for 3 h on ice before incubation with the probe.…”
Section: Electrophoretic Gel Mobility Shift Assay (Egmsa)mentioning
confidence: 99%
“…Random site selection has suggested that additional nonconsensus sequences can bind GATA proteins with high affinity (32,42). Two of the GATA transcription factors (GATA-1 and GATA-3) are expressed in a tissuerestricted fashion and have been shown previously to regulate lineage-specific gene expression in erythroid cells and T lymphocytes, respectively (24,29,33,72,78). Moreover, homozygous disruption of the GATA-1 gene in mice results in a specific block in erythroid development (56,68).…”
mentioning
confidence: 99%